Practitioner experience of the impact of humanistic methods on autism practice: a preliminary study. Issue 2 (20th August 2020) - Robinson, Anna; Galbraith, Ian; Carrick, Lorna
Abstract : Purpose: Autistic people are subject to having their behaviour shaped from a variety of practitioners predominantly using behaviourist methodologies. Little is known about how learning alternative humanistic methodologies impacts practitioner experiences of relational encounters with autistic people. This paper aims to develop an understanding of practitioner experiences of using person-centred counselling (PCC) skills and contact reflections (CR) when engaging with autistic people. Design/methodology/approach: This qualitative study used an interpretive approach to help elucidate perceptions of changing practice. It involved a framework analysis of 20 practitioner's experiential case study accounts. Findings: An overarching theme emerged: subtle transformations resulted from shifting practice paradigms. Four broad themes were identified: "A different way of being"; "Opening heightened channels of receptivity"; "Trust in self-actualising growth" and "Expanding relational ripples". The findings suggest that PCC and CRs skills training shows promise in providing practitioners with a different way of being with autistic people that enhances their capacity towards neurotypical-neurodivergent intersubjectivity. Social implications: The authors speculate on the power dynamics of care relationships and those who may identify as possessing autism expertise. The authors are curious as to whether this humanistic skills training can truly penetrate practitioner core values and see this as a fundamental issue which requires further investigation. Originality/value: To the best of the authors' knowledge, this is the first study to provide a qualitative account of autism practitioner reflections following training in humanistic methodologies. It challenges the concept of autism expertise, guided by a pathologiSing model, focused on fixing a problem located in the person, which conceals the removal of personhood.